Fertility and early-life mortality: Evidence from smallpox vaccination in Sweden - Philipp Ager; Casper Worm Hansen; Peter Sandholt Jensen (European Historical Economics Society (EHES), 2014)
We examine how the introduction of smallpox vaccination affected early-life mortality and fertility in Sweden during the first half of the 19th century. We demonstrate that parishes in counties with higher levels of smallpox mortality prior to the introduction of vaccination experienced a greater decline in infant mortality afterwards. Exploiting this finding in an instrumental-variable approach reveals that this decline had a negative effect on the birth rate, while the number of surviving children and population growth remained unaffected. These results suggest that the decline in early-life mortality cannot account for the onset of the fertility decline in Sweden.
Keywords: J10; J13; I15; 330; Fertility transition; infant mortality; smallpox vaccine